The mTOR inhibitor rapamycin suppresses trigeminal neuropathic pain and p-MKK4/p-p38 mitogen-activated protein kinase-mediated microglial activation in the trigeminal nucleus caudalis of mice with infraorbital nerve injury - Yeo, Ji-Hee; Roh, Dae-Hyun (Frontiers in Molecular Neuroscience, 2023)
Neuropathic pain caused by trigeminal nerve injury is a typical refractory orofacial chronic pain accompanied by the development of hyperalgesia and allodynia. We previously demonstrated that the mammalian target of rapamycin (mTOR) inhibitor rapamycin suppressed orofacial formalin injection-induced nociception; however, the underlying mechanism is unclear, and it is unknown whether it can reduce trigeminal neuropathic pain. In mice, left infraorbital nerve and partial nerve ligation (ION-pNL) was performed using a silk suture (8–0). Fourteen days after surgery, neuropathic pain behavior was examined on a whisker pad and rapamycin (0.1, 0.3, and 1.0 mg/kg) was administered intraperitoneally. Mechanical and cold sensitivities in the orofacial region were quantified using von Frey filaments and acetone solution, respectively. Changes in mTOR and related proteins, such as p-MKK3/6, p-MKK4, p-JNK, p-ERK, p-p38 MAPK, GFAP, and Iba-1, in the trigeminal nucleus caudalis (TNC) or the trigeminal ganglia (TG) tissues were examined via western blot analysis or immunohistochemistry. Mice demonstrated significant mechanical and cold allodynia 2 weeks following ION-pNL injury, both of which were significantly reduced 1 h after the administration of high-dose rapamycin (1.0 mg/kg). In the TG tissue, ION-pNL surgery or rapamycin treatment did not change p-mTOR and p-4EBP1, but rapamycin reduced the increase of p-S6 and S6 induced by ION-pNL. In the TNC tissue, neither ION-pNL surgery nor rapamycin treatment altered p-mTOR, p-S6, and p-4EBP1 expressions, whereas rapamycin significantly decreased the ION-pNL-induced increase in Iba-1 expression. In addition, rapamycin suppressed the increase in p-p38 MAPK and p-MKK4 expressions but not p-MKK3/6 expression. Moreover, p-p38 MAPK-positive cells were colocalized with increased Iba-1 in the TNC. Our findings indicate that rapamycin treatment reduces both mechanical and cold orofacial allodynia in mice with trigeminal neuropathic pain, which is closely associated with the modulation of p-MKK4/p-p38 MAPK-mediated microglial activation in the TNC.